Keterlaksanaan Pendidikan Agama Buddha Dalam Implementasi Kurikulum 2013 - Hesti Sadtyadi (Purwadita : Jurnal Agama dan Budaya, 2020)
This study aims to determine how the process of applying the  curriculum 2013 of Buddhist education in primary and secondary education, and how the output of Buddhist education, at primary and secondary levels. This research is an evaluation research. In this study the methodology tends to use a qualitative evaluation. The results of this study indicate that the process of Buddhist education in primary and secondary education, in the application of the curriculum 2013, has gone quite well. That the school has aligned needs for the learning process. The material and teaching material have been integrated with the objective component, which is explicitly written, and students have an interest, positive attitude in learning Buddhist subjects. The output of Buddhist education at the elementary and secondary levels, in the application of the curriculum 2013, has had a quantity of achievements according to the objectives (output) of learning, with the achievement of good grades. All students in learning succeed well. Keywords: Evaluation, Curriculum, Buddhist Education